Determination of the physicochemical and microbiological quality of buffalo milk in the south of lake Maracaibo - Luis Álvarez; Alexis Zambrano; Datty Rosales-Zambrano (Revista Científica)
The determination of quality parameters in the food industry is a critical point in the transformation process in aspects such as safety and quality attributes required by the market for a product, the cheese making industry does not escape this. In Venezuela, the standards for raw materials (raw milk) and dairy derivatives are established by COVENIN (Venezuelan Commission of Industrial Standards), which determine variables of great importance in milk such as: lipids, proteins, lactose, mineral salts, load microbial, among others. These components are of great importance because they influence the entire production chain. The purpose of this work is to evaluate the physicochemical and microbiological quality of buffalo milk used in a lactuary in western Venezuela, according to the official regulations in force in the country. It was developed at the Chemical, Industrial and Agricultural Analysis Research Laboratory (LIAQIA), in conjunction with the Venezuelan dairy company CONLAC and the VATCA Laboratory. C.A., (Biodiagnostic Unit), in order to provide the company with quality controls on cheeses made from buffalo milk. Sampling of raw pure milk (production units described as A, B, C and D) and milk mixtures (composite samples described as E) and pasteurized milk F was carried out consecutively for three months in 2019. Samples of Milk was taken in triplicate from the tanks according to the COVENIN 938-1983 standard, from the four buffalo production units in the southern area of Lake Maracaibo, collecting 400 mL of milk for each sample, in taking the milk sample. it was homogenized for 5 minutes by stirring. A completely randomized experimental design was carried out, where the parameters evaluated were the mean (x̄), the standard deviation (S), coefficient of variation (CV), Tukey’s post hoc tests using the statistical program Minitab 15 V. 2021. The analyses physicochemical tests were performed on buffalo milk, where the parameters of acidity, fat, solid non-fat (SNG), lactose, protein, and cryoscopy were evaluated in the milk. Some of the mentioned tests were performed directly using a Lactoscan. The amount of somatic cells was determined for each milk sample by direct microscopic somatic cell count (CCS) and bacterial colony count in a Petri dish (COVENIN 1126-1989, COVENIN 902-1987 and García, 2011). The average physicochemical values of the three raw milk samples from farms evaluated were for A, B, C and D respectively: Acidity: 17.1 ± 0.8**; 17.67 ± 0.5*; 16.8 ± 0.7*; 17.6 ± 0.5*; % Fat: 5.2 ± 0.4**; 6.5 ± 0.4**; 6.4 ± 0.5**; 6.6 ± 0.1**; Solid non-fat (SNG): 9.3 ± 0.1*; 9.7 ± 0.2*; 9.9 ± 0.2**; 9.7 ± 0.2*; Lactose: 5.1 ± 0.1*; 5.3 ± 0.1*; 5.4 ± 0.1**; 5.3 ± 0.1*; % Protein: 4.14 ± 0.03*; 4.21 ± 0.04*; 4.25 ± 0.04*; 4.27 ± 0.06*; and Cryoscopy: 0.61 ± 0.01*; 0.64 ± 0.01*; 0.66 ± 0.02**; 0.65 ± 0.02*: The averages of the samplings of the milk mixtures E (milk silo) and F (pasteurized milk) obtained: Acidity: 17.6 ± 0.5*; 18.3 ± 0.7*; % Fat: 6.0 ± 0.2**; 3.9 ± 0.6**; SNG: 9.7 ± 0.2**; 8.1 ± 0.6**; Lactose: 5.3 ± 0.1**; 4.4 ± 0.3**; % Protein: 4.16 ± 0.03*; 3.7 ± 0.3** and Cryoscopy: 0.64 ± 0.02**; 0.51 ± 0.04**. (**) Presents a significant difference between the results obtained during the three months of sampling (Tukey, p < 0.05). The somatic cell count (CCS) of farms A, B, C and D were: 103,937, 162,271, 101,842 and 306,816 (cells/mL) respectively. The colony forming units for farms A, B, C, D and E were: 1.2 x 106; 2 x 105; 6.6 x 105; 8.9 x 106; 1.3 x 107 (CFU/mL) respectively. It is concluded that buffalo milk in the southern area of Lake Maracaibo is affected by the month in which the sample is taken, especially the percentage of milk fat. The most outstanding properties of buffalo milk is its high fat content, which presents an average value of 6.0 ± 0.2% fat; Another outstanding value is the amount of protein around 4.16 ± 0.03%. The microbiological quality indicators indicate that the processes for obtaining milk must be improved and framed in practice that guarantee the safety of raw milk.